2006
DOI: 10.1021/ja062031l
|View full text |Cite
|
Sign up to set email alerts
|

New Limits for Solid-State 17O NMR Spectroscopy:  Complete Resolution of Multiple Oxygen Sites in a Simple Biomolecule

Abstract: Nuclear magnetic resonance (NMR) is a key technique in providing atomic scale information on molecular architecture. Solidstate NMR approaches are playing an increasing role in biomolecular science; however, almost all such NMR reports concern spin-1/2 nuclei ( 1 H, 13 C, 15 N). Oxygen is one of the most important and abundant elements in biological systems, 1 but it is little studied by NMR. Since oxygen plays a central role in many biological interactions, such as protein-protein, metal-protein, and in nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 18 publications
1
26
0
Order By: Relevance
“…In particular, recent demonstrations on 17 O DOR spectroscopy have reported ultra-high spectral resolution with linewidths of <1 ppm). [15][16][17][18][19][20][21] It is worth noting that high-resolution 17 O NMR MQMAS and DOR have also been reported for many important inorganic materials. 5,[22][23][24] In comparison to inorganic materials, there are three major complications for 17 O solid-state NMR on bio/organic molecules: (1) the abundance of hydrogen in bio/organic molecules gives rise to significant dipolar broadening unless high power 1 H-decoupling is applied; (2) the quadrupole interaction is generally larger (7- 33 was used.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, recent demonstrations on 17 O DOR spectroscopy have reported ultra-high spectral resolution with linewidths of <1 ppm). [15][16][17][18][19][20][21] It is worth noting that high-resolution 17 O NMR MQMAS and DOR have also been reported for many important inorganic materials. 5,[22][23][24] In comparison to inorganic materials, there are three major complications for 17 O solid-state NMR on bio/organic molecules: (1) the abundance of hydrogen in bio/organic molecules gives rise to significant dipolar broadening unless high power 1 H-decoupling is applied; (2) the quadrupole interaction is generally larger (7- 33 was used.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have been reported utilizing DOR NMR for the differentiation of sodium, boron, aluminium and oxygen sites in minerals [9][10][11], materials [12][13][14][15][16] and molecular sieves, including, zeolites [17][18][19][20], sodalites [21][22][23] and aluminophosphates [24][25][26][27][28]. Recently, focus has turned to exploiting DOR for the study of oxygen sites in organic solids [29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of DOR NMR studies reported have been concerned with the differentiation of sodium, boron, aluminium and oxygen sites in minerals [18][19][20], materials [21][22][23][24][25] and molecular sieves, including, zeolites [26][27][28][29], sodalites [30][31][32] and aluminophosphates [33][34][35][36][37]. More recently, focus has turned to exploiting DOR for the study of oxygen sites in organic solids [17,[38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%